2020
DOI: 10.1002/htj.21849
|View full text |Cite
|
Sign up to set email alerts
|

Stability and thermophysical properties of fly ash nanofluid for heat transfer applications

Abstract: Improving the performance of heat transfer fluids is altogether significant. The best approach for improving the thermal conductivity is the addition of nanoparticles to the base fluid. In the present study, specific heat, dynamic viscosity, and thermal conductivity of water-based Indian coal fly ash stable nanofluid for 0.1% to 0.5% volume concentration in the temperature range of 30 to 60°C has been investigated. To evaluate an average particle diameter of 11.5 nm, the fly ash nanoparticles were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…37 If the absolute value of ζ lies between ±30 and 40 mV was stable, ±40 and 60 mV had good stability, above 60 mV has excellent stability, and less than ±30 mV was agglomerative. 38,39 In the present study, the ζ was measured using a Zeta sizer (Malvern Instruments) at 25°C for 0.5 vol% concentration of different particle sizes at a pH of 7.5-8.…”
Section: Stabilitymentioning
confidence: 99%
“…37 If the absolute value of ζ lies between ±30 and 40 mV was stable, ±40 and 60 mV had good stability, above 60 mV has excellent stability, and less than ±30 mV was agglomerative. 38,39 In the present study, the ζ was measured using a Zeta sizer (Malvern Instruments) at 25°C for 0.5 vol% concentration of different particle sizes at a pH of 7.5-8.…”
Section: Stabilitymentioning
confidence: 99%
“…From the study, it was observed that 10.29% enhancement in viscosity was found for 2% of weight concentration at 20°C compared with base fluid. Brownian motion and van der Waals forces are the primary contributors 53,54 for the increase in viscosity of nanofluid. Accordingly, for 0.2, 0.5, 1, and 1.5 wt% concentration, the CHTC obtained was 6.43%, 14.25%, 23.61%, and 28.94% greater than that of base fluid respectively.…”
Section: Viscositymentioning
confidence: 99%
“…The thermal conductivity of nanofluids increased with temperature and concentration. Other nanofluids thermal conductivity coefficiencies, for instance, the ash nanofluids thermal conductivity and viscosity would increase, but the specific heat would decrease when the volume concentration increased 29 30 and the results indicated the TPF thermal performance factor values increased with the concentration increasing.…”
Section: Introductionmentioning
confidence: 98%
“…Other nanofluids thermal conductivity coefficiencies, for instance, the ash nanofluids thermal conductivity and viscosity would increase, but the specific heat would decrease when the volume concentration increased. 29 The researcher studied the heat transfer, entropy generation and pressure drop of fly ash-Cu hybrid nanofluid under turbulent flow in a tube, 30 and the results indicated the TPF thermal performance factor values increased with the concentration increasing.…”
Section: Introductionmentioning
confidence: 99%